How are 1, 2, 3-triazoles accommodated in helical secondary structures?. Issue 19 (25th April 2018) - Ben Haj Salah, Khoubaib; Das, Sanjit; Ruiz, Nicolas; Andreu, Vanessa; Martinez, Jean; Wenger, Emmanuel; Amblard, Muriel; Didierjean, Claude; Legrand, Baptiste; Inguimbert, Nicolas
Abstract : Peptaibols were used as templates to monitor the impact of 1, 2, 3-triazole (Tz) insertion in place of amide bonds in a helix structure. Abstract : 1, 4-Disubstituted-1, 2, 3-triazole (Tz) is widely used in peptides as a trans -amide bond mimic, despite having hazardous effects on the native peptide activity. The impact of amide bond substitution by Tz on peptide secondary structures is scarcely documented. We performed a Tz scan, by systematically replacing peptide bonds following the Aib residues with Tz on two model peptaibols: alamethicin F50/5 and bergofungin D, which adopt stable α- and 310 helices, respectively. We observed that the Tz insertion, whatever its position in the peptide sequences, abolished their antimicrobial activity. The structural consequences of this insertion were further investigated using CD, NMR and X-ray diffraction. Importantly, five crystal structures that were incorporated with Tz were solved, showing various degrees of alteration of the helical structures, from minor structural perturbation of the helix to partial disorder. Together, these results showed that Tz insertions impair helical secondary structures.